Disrupting Human Resource Development by Digital Literacy - Watthanabut, Busakorn; Chiwattanakorn, Trakul (Journal of International Buddhist Studies, 2019)
This academic writing will be represented about the important of human resource development in the digital era when the believe were in the concept based on talent and ideas rather than capital that have become to the key factors affecting the growth of most large enterprises. It always drives individual , business and society forward, propelling them towards achieving company vision and sustainable development goals. Most of all serves as an additional issue to be considered, supplementing fundamental topic such as workforce planning commensurate to business’ growth, increasing work capacity to maximize employment value. Based on the increasing level of competition, the use of technology in doing business has increased. The important thing makes quality of human resource that believes that good development of human resource ensures productive synergies in the workplace, lifts social bonding and working spirit, looks for environments that espouse this mind-set, allows for creative work and retains personnel with the organization which in turn moves an organization and its personnel and serving as a factor inaugurating in Thailand company.